2022
DOI: 10.1371/journal.pone.0276717
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic acid treatment ameliorates the cardiac dysfunction in NASH mice

Abstract: Background Suppression of cardiac iinflammasome, which can be inhibited by Farnesoid X receptor (FXR) agonist, can ameliorate cardiac inflammation and fibrosis. Increased cardiac inflammasome decrease the abundance of regulatory T (Treg) cells and exacerbate cardiac dysfunction. Interaction between cardiomyocytes and Treg cells is involved in the development of nonalcoholic steatohepatitis (NASH)-related cardiac dysfunction. Aims This study evaluates whether the FXR agonist obeticholic acid (OCA) treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Obeticholic acid is a potent selective FXR agonist, currently approved for PBC patients as a second-line treatment [ 211 ]. Due to its possible therapeutic application in NAFL/NASH, several studies have been performed to evaluate obeticolic acid efficacy in different animal models [ 212 , 213 , 214 , 215 , 216 , 217 , 218 ], showing a reduction in liver lipid content, oxidative stress, and fibrosis. The results obtained from obeticolic acid in clinical trials on NASH noncirrhotic patients showed a significant improvement in NASH score, fibrosis, lobular inflammation, and steatosis in the treated group [ 219 ].…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%
“…Obeticholic acid is a potent selective FXR agonist, currently approved for PBC patients as a second-line treatment [ 211 ]. Due to its possible therapeutic application in NAFL/NASH, several studies have been performed to evaluate obeticolic acid efficacy in different animal models [ 212 , 213 , 214 , 215 , 216 , 217 , 218 ], showing a reduction in liver lipid content, oxidative stress, and fibrosis. The results obtained from obeticolic acid in clinical trials on NASH noncirrhotic patients showed a significant improvement in NASH score, fibrosis, lobular inflammation, and steatosis in the treated group [ 219 ].…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%